Range of outputs precise of digits rounding in SPSS and MS Excel - Al-Hashami, Zaher (Journal of Advanced Computer Science & Technology, 2014)
The statistical operations done by many specialist programs, by them can do these operations fluently and precisely. There are many functions in such programs can calculate in SAS, STAT and the analytical program SPSS. There is Microsoft Excel program that is calculate like these functions. The level of some programs may be different than others within these functions they are calculating. From these functions are Sum, Average, Maximum and Minimum. Round function is also from these functions that can measure it's accuracy through this research. In this research i chose ten digits numbers and I also chose three criteria under, equal and more than 5. According to that the rounding operations are done based on if wanted decimal place is less, equal or higher than 5. Rounding applied on ten digits using SPSS and MS Excel programs. The outputs findings are the same except that Microsoft Excel is truncating the last zeroes of the digit after the decimal point. Wherever the decimal place specified in the digit is want it will truncate after the decimal point. The SPSS is more precise than MS Excel based on the decimal place in the digit number wanted statistically and analytically.Keywords: Decimal Place, Digit, Excel, Function, Round.